Persistence of antibodies to pneumococcal conjugate vaccine compared to polysaccharide vaccine in patients with Crohn's disease – one year follow up. Issue 9 (2nd September 2019) - Kantsø, Bjørn; Halkjær, Sofie Ingdam; Østergaard Thomsen, Ole; Belard, Erika; Gottschalck, Ida Benedikte; Jørgensen, Charlotte Sværke; Krogfelt, Karen A.; Slotved, Hans-Christian; Ingels, Helene; Petersen, Andreas Munk
Abstract: Background: Patients suffering from Crohn's disease (CD) are at increased risk of infectious diseases, such as pneumococcal infection. The risk increases with immunotherapy. Pneumococcal infection can be prevented by vaccination. Methods: We conducted a randomized trial of the 23-valent pneumococcal polysaccharide vaccine (PPV23) and the 13-valent pneumococcal conjugated vaccine (PCV13) in groups of CD patients treated with immunosuppressive (IS) drugs in the form of thiopurines (PPV23 n  = 28, PCV13 n  = 28) alone or in combination with TNF-α antagonists (PPV23 n  = 13, PCV13 n  = 13) and CD patients not treated with any of these drugs (untreated) (PPV23 n  = 30, PCV13 n  = 24). In this article, we report the immunogenicity of PPC23 and PCV13 one year after vaccination. Results: No overall differences in vaccine-induced serotype-specific immunoglobulin G (IgG) antibodies or functional antibodies (opsonophagocytic activity (OPA)) were found between the two vaccines. PCV13 induced a higher concentration of IgG antibodies for serotype 9V than PPV23 in untreated patients. In contrast, PPV23 induced higher OPA for serotypes 6B and 19F than PCV13 in IS treated patients. Untreated patients showed generally higher IgG and OPA antibody levels than patients treated with IS and TNF-α antagonists. Conclusions: In conclusion, we found no general differences in the persistence of induced antibodies when comparing PPV23 with PCV13 regardless of treatment and also within treatment groups (IS, IS + TNF-α and untreated). This was demonstrated for both serotype-specific IgG antibodies and as functional antibodies (OPA). Patients treated with thiopurines in combination with TNF-α inhibitors have an impaired immune response against both PPV23 and PCV13, as compared to untreated patients. This study has been registered in the European Clinical Trials Database (EudraCT, record no 2012-002867-86) and ClinicalTrials.gov (record no. NCT01947010). Trial registration: ClinicalTrials.gov identifier: NCT01947010.